Analisis Kinerja Pengelolaan Data ASN pada Subbagian Kepegawain di Dinas Pendidikan Prov Sumsel - Cica Serioktawa; Sri Rahayu (CV. Shofanah Media Berkah, 2025)
Civil Servant (ASN) data management is a crucial aspect in supporting the effectiveness of personnel administration in government agencies. However, in practice, ASN data management often faces obstacles such as delays in data updates, discrepancies between physical and digital archives, and suboptimal utilization of the personnel information system. This study aims to analyze the performance of ASN data management in the Personnel Subdivision of the South Sumatra Provincial Education Office using a qualitative descriptive approach. Data were obtained through observation, interviews, and documentation studies during the Field Work Practice (PKL). The results indicate that although the personnel information system has helped expedite administrative processes, several obstacles remain, such as a lack of data integration, late reporting from work units, and suboptimal archive digitization. This study provides recommendations for improving employee competency, optimizing the personnel information system, and simplifying administrative processes to enhance the effectiveness of ASN data management.